A STRUCTURAL DISCOURSE ANALYSIS OF THE ADVERTSISMENT OF “JOB CAREER “ IN THE BATAM POS DAILY NEWSPAPER - Suswanto Ismadi Megah (Universitas Riau Kepulauan, 2015)
In recent days the advertisement is a most effective way to sell or to market new products of the businessmen or producers. Due to the case, advertisement has great role in selling or marketing of the product. The producers use interesting advertisements to introduce their product by using interesting or different language style. This study focuses on the structural discourse of the advertisement used in Batam Pos daily newspaper in Batam island. Sample of the data obtained from job career column in January 2013. The advertisement consist of the opening, the body and the closing of the advertisement.